Risk Management of International Trade in the Context of BRI: A Case study of DF Company in China - Ren, Zhaoxia (Pacific International Journal, 2024)
The study explores the intricate landscape of global commerce, focusing on the evolving challenges and opportunities in international business. The study centers on DF Company, a prominent Chinese engineering contracting firm, and analyzes its risk management practices in the context of the Belt and Road initiative. The Belt and Road strategy, with its goals of policy coordination, infrastructure connectivity, trade facilitation, currency circulation, and people-to-people bonds, presents both historical continuity and new opportunities for international trade. The research adopts a qualitative case study design, delving into DF Company's operations through interviews, document analysis, and direct observation. The findings reveal that DF Company faces multifaceted challenges in managing international trade risks, particularly in the areas of political, policy, social, technological, and cultural risks. The paper concludes with comprehensive recommendations for DF Company, emphasizing proactive risk management, political risk mitigation, adaptation to policy changes, addressing social risks, technological capability enhancement, cultural risk management, and safety measures in conflict-prone areas. These recommendations aim to strengthen DF Company's international trade risk management framework within the Belt and Road initiative.